GLOBALIZATION AND THE NEW PARTNERSIDP FOR AFRICA'S DEVELOPMENT (NEPAD): RELEVANCE FOR SOCIAL WORK - Sewpaul, V (Social Work/Maatskaplike Werk, 2005)
The neo-liberal ideology that underscores the New Partnership for Africa's Development (NEPAD), rather than providing strategies for the salvation of Africa holds the possibility for further marginalisation of the poor, for entrenching inequality, and for worsening the plight of the most vulnerable of our society. Social workers are expected to work against poverty, and towards sustainable people-centred development. Yet, macro economic policies and strategies seem to be designed to work against these objectives. NEPAD, instead of representing the interests and the will of the African people, serves more the interests of the world capitalistic order, with African leaders capitulating to the demands of the G8 and to the international financial institutions. Despite their active roles in perpetuating poverty and inequality, there is the protest from government that the welfare sector, and social work more specifically, lacks the skills and expertise to achieve the objectives of poverty alleviation and sustainable development. As social work educators and practitioners, we need to critically interrogate those factors that impact the welfare sector and social work, and that deny people the opportunities for survival, let alone gainful and healthy living. As international social work and global movements around anti-oppressive practice, human rights and social justice evolve, social work must meet its ethical obligations in respect of collective responsibility and collective action.